Community pharmacists' knowledge, attitude, and nonprescription dispensing practices of antibiotics: An explorative study in a selected city of South India - K Sarath Kumar; S Saranya; Nagasubramanian Vanitha Rani (Wolters Kluwer Medknow Publications, 2022)
Objective: This study aimed to assess the community pharmacists' knowledge of antibiotics, their attitude toward antibiotic usage and antibiotic resistance, and their nonprescription dispensing practices of antibiotics. Methods: A cross sectional-questionnaire-based study was conducted among 75 community pharmacists practicing in a selected city of South India. Data on their age, years of experience, and educational qualifications were obtained. A modified, 33-items, prevalidated structured questionnaire was used to assess the community pharmacists knowledge, attitude, and nonprescription antibiotic dispensing practices knowledge, attitudes and practices (KAP). The responses obtained were expressed in descriptive statistics. The association between years of experience and their KAP was assessed using Pearson's correlation. Findings: Most pharmacists (60%) agreed that antibiotics are used for bacterial infections, and 35% believed that antibiotics could be given for pain and inflammation. Fourty-one percentage of pharmacists agreed that dispensing antibiotics without prescription increases the risk of antibiotic resistance. Seventy-two percentage agreed that they are responsible for taking a prominent role in antimicrobial resistance and infection-control programs in healthcare. Only 46% of pharmacists stated that they always dispensed antibiotics only with a prescription, and 56% dispensed antibiotics for longer than the doctor prescribed. Amoxicillin, metronidazole, and cephalexin were the most commonly dispensed antibiotics without a prescription. The most common reason for dispensing antibiotics without a prescription was the fear of losing customers. Conclusion: The study identified an average KAP interquartile range 1 among community pharmacists, indicating a lack of awareness of antibiotic resistance and dispensing antibiotics without a prescription.